Hormone replacement therapy effects on the hemostatic system - Soszka, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
The current literature on HRT effects on hemostasis has been reviewed. Changes within the coagulation and fibrinolytic system in menopause as well as effects of estrogens and gestagens on particular constituents of the hemostatic system have been described. Several aspects of HRT effects on vessel diseases, in particular on artherosclerosis and venous thrombembolic disease have been discussed. The influence of HRT on hemostasis in terms of the route of application has been compared. Special attention has been paid to different results of a vast number of studies investigating HRT effects on vessels and hemostatic markers as well as to contradictions of the results of epidemiological, clinical and basic studies.